2019
DOI: 10.1002/qua.25932
|View full text |Cite
|
Sign up to set email alerts
|

Small binary iron‐carbon clusters with persistent high magnetic moments. A theoretical characterization

Abstract: Characterization of the structural and electronic properties of binary iron‐carbon clusters composed by six iron atoms and with up to nine carbon atoms was carried out with density functional theory calculations. Neutral, cations (q = +1), and anions (q = −1), some of them experimentally detected, were studied. The formation of dimers and trimers of carbon atoms over the iron surface were preferred. Moreover, some large carbon chains, with up to five atoms, were determined. High spin states emerged for the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 89 publications
4
27
0
Order By: Relevance
“…48 Additionally, the density functional theory studies have reported that the iron carbide clusters show the magnetic moment of ca. 1-3.5 m B atom Fe À1 , [30][31][32] which is consistent with those in this study. Therefore, with consideration of the magnetic moment and the Curie temperature, it was concluded that the magnetic behavior of the iron carbide cluster samples is derived from the carbides themselves, and not from impurities.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…48 Additionally, the density functional theory studies have reported that the iron carbide clusters show the magnetic moment of ca. 1-3.5 m B atom Fe À1 , [30][31][32] which is consistent with those in this study. Therefore, with consideration of the magnetic moment and the Curie temperature, it was concluded that the magnetic behavior of the iron carbide cluster samples is derived from the carbides themselves, and not from impurities.…”
supporting
confidence: 93%
“…2 nm, 7,16 aside from the gas phase experiments 26,27 and the theoretical studies. [28][29][30][31][32] In these cases, the iron carbide nanoparticles exhibit superparamagnetism, i.e., they do not act as magnets at ambient temperature. However, sub-nanosized iron carbide particles have remained elusive to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…50 Persistent high magnetic moments have already been reported for mixed iron−carbon clusters. 49 For instance, Nash et al 22 studied FeC 1−3 neutral species within DFT, at the local density approximation, and fourth-order Møller− Plesset perturbation theory. Independently of the number of carbon atoms bonded to iron, FeC 1−3 clusters are found with triplet and quintet multiplicities and, consequently, magnetic moment comparable to that found for iron in its atomic ground state.…”
Section: Introductionmentioning
confidence: 99%
“…52 From all of the above, this work aims, based on previous studies about small pure iron 3 and iron−carbon clusters, 9,51 to extend the knowledge on mixed iron−carbon clusters. In this sense, density functional theory (DFT) calculations have proven 49,51 to provide reliable results, being comparable to the most expensive wavefunction-based quantum chemistry methods. 15 2.…”
Section: Introductionmentioning
confidence: 99%